Education for sustainable development in higher education: State-of-the-art, barriers, and challenges - Gonzalo Fernandez-Sanchez; María Olga Bernaldo; Ana Castillejo; Ana María Manzanero (Laureate Education Inc, 2014)
Education for Sustainable Development (ESD) is a new educational paradigm that allows Universities to lead and respond to social needs towards a more sustainable life. The ESD is a global preparedness and complex phenomena in relation to the effects of human activity on the environment, society and economy in spatial (global, regional and local) and temporal dimensions (learn from the past, act in the present and anticipate the future). This essay provides an important synthesis of the vast literature in recent years in relation to ESD. It analyzes the areas and elements to be integrated into the application and integration of Sustainability in Higher Education (SHE), the importance of sustainability curricula and changing the teaching and learning methods into more participative and active techniques. The essay ends with a proposal of steps to follow to implement a sustainability plan, the various existing integration strategies, and the identification of barriers and remaining challenges into ESD. DOI: 10.18870/hlrc.v4i3.157